Implementation of Policy and Manifestation of Cultural Values in Handling Covid-19 at the North Jakarta Mayor's Office - Riskawati, Reni (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This research was conducted to analyze the Implementation of Policy and Manifestation of Cultural Values in Handling Covid-19 in the North Jakarta Mayor's Office, DKI Jakarta Province. The research method used is a qualitative research method with the ASOCA (Ability, Strength, Opportunity, Culture, Agility) analysis approach. The qualitative research method is an appropriate method for uncovering current problems in the case of handling Covid-19 in DKI Jakarta in particular and in Indonesia in general. The qualitative method is a very appropriate method in this case because data processing is carried out in the form of words and not in numerical form. Based on the research results, it shows that the role of vaccination, Micro PPKM, ideology in cultural values has a very significant and positive influence on the handling of Covid-19 in the North Jakarta Mayor's Office, DKI Jakarta Province